(untitled) (Journal of Economic Research & Business Administration, 2016)
In this article the foreign experience of state regulation of innovative projects at the regional level. Comparative analysis of the experience of developed countries shows that in many countries formed a countermovement «from the center to the regions» and «from the regions to the center.» There is a spontaneous process of searching for innovative models of regional development, while the process of the search model of innovative development «from above», at the level of national governments. And if at the level of regions dominated by attempts to real action on the transfer of development economics with virtually no experience with the formation of a model to be emulated in other regions, the level of federal centers dominate the discussion, debate, construction of theoretical models with a significant lack of real action in relation to the region in the direction of helping them to change the structure of their economies.